Hospitalization of newborns and young infants for chickenpox in France - Lécuyer, Aurélie (Eur J Pediatr, 2010)
Chickenpox is often considered more severe during the first year of life, but its course is usually mild during the first 3 months of life, presumably owing to the persistence of maternal antibodies. Hospitalization and intravenous acyclovir therapy are generally restricted to severe cases but also systematically recommended in newborns in France, irrespective of the clinical severity of the infection. This recommendation was launched in 1998 when Varicella zoster virus (VZV)-specific immunoglobulins were not available in the country and has remained unchanged since. The aim of this prospective observational study was to describe complications of varicella infection in a population of 745 children hospitalized for varicella before 1 year of age, with a specific focus on newborns. Complications occurred in 65% of cases. They were very rare before the age of 1 month (10%) but their incidence then increased progressively with age and probably the disappearance of maternal antibodies: 42% (1–2 months), 66% (3–5 months), 70% (6–8 months), and 79% (9–12 months). Conclusion Chickenpox is usually mild in newborns because most of them are protected by VZV maternal antibodies. Unless the absence of maternal VZV immunity is demonstrated, newborns with mild chickenpox should not require antiviral therapy.